Education on Maintaining an Ideal Body Weight to Reduce the Risk of Diabetes Mellitus Among Students at Al-Azhar Private High School in Medan - Aritonang, Barita; Syarifuddin, Shofian; Harahap, Hasni Yaturramadhan; Wiratma, Dicky Yuswardi; Marbun, Romauli Anna Teresia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Diabetes Mellitus (DM) is a chronic condition with increasing prevalence worldwide, including in Indonesia, where the number of affected individuals reached 10.7 million in 2021. One of the main factors contributing to the rising risk of DM in adolescents is obesity, often influenced by unhealthy lifestyle habits. Therefore, education on maintaining an ideal body weight is essential to prevent DM in this age group. This Community Service Program aims to educate the students of SMA Swasta Al-Azhar Medan about the importance of maintaining an ideal body weight to prevent DM. The program combines lectures, interactive discussions, and hands-on activities. It includes a pre-test, educational content delivery, practical exercises, and a post-test. 100 students participated, covering topics such as the relationship between body weight and DM, healthy eating habits, physical activity, and how to monitor weight and calculate Body Mass Index (BMI). The results show significant improvements in students' knowledge about DM, healthy eating, and physical activity. Knowledge of DM increased by 45.5%, understanding of healthy eating improved by 26.1%, and awareness of physical activity grew by 24.3%. Additionally, the average BMI of students decreased by 2.4%, indicating positive lifestyle changes. In conclusion, the program successfully improved students' understanding and encouraged behavioral changes to prevent DM. The increase in knowledge, healthier eating habits, greater physical activity, and reduction in BMI highlight the effectiveness of the educational approach. This program can potentially serve as a model for promoting healthy lifestyles to prevent DM in adolescents.